Artificial Intelligence dalam Etika Penulisan Karya Ilmiah di Kalangan Mahasiswa Universitas Muhammadiyah Ponorogo - Utari, Prahastiwi; Anggreni, Likha Sari; Alkhajar, Eka Nada Shofa; Tanti Hermawati; Yudiningrum, Firdastin Ruthnia; Surwati, Chatarina Heny Dwi; Pramana (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
Artificial Intelligence (AI) studies how to make computers do the same or even better than humans. In the academic world, the convenience created by AI can only be separated from negative impacts if its use is balanced with an understanding of its users. Potential ethical violations in writing scientific papers lurk if AI is not understood with clear boundaries. Plagiarism, data validity, and personal data security are potential ethical violations among students when using AI in writing work. Responding to the existing concerns, the Research Group Media, Audiences and Socio-Cultural Systems of the Faculty of Social and Political Sciences, Sebelas Maret University held a workshop entitled Building Scientific Awareness: Artificial Intelligence in the Ethics of Writing Work among Communication Science Students at Muhammadiyah Ponorogo University. Targeting students who will enter the stage of writing their final project in the form of a thesis, Muhammadiyah Ponorogo University was chosen because it is a developing private campus that needs to be encouraged to achieve superior quality. In the workshop, students showed enthusiasm in following every material presented by the speakers. A survey conducted at the end of the session showed that students' understanding and experience could provide clear boundaries regarding the ethics of scientific writing in the era of AI technolog.